Transport design Proton in 2050 / Nur Nazlin Zahri - Zahri, Nur Nazlin (Universiti Teknologi MARA, Kedah, 2018)
Transportation is the main servent to human being in this modern day in terms of traf-ficking them.Transports have been widely used either in public services or even personal use. Based on our research, criteria that is acceptable and applieable is modern as the way of living, luxury for some concepts installed and simple to delicate the user's inter-pretation. The main focus of transportation is for the ease of movement from one place to another. But there are also some high demands that focus on the elegance and the beauty of ride. The purpose of this study is to come out with an idea of a new design to be applied onto the next generation of Proton's family. The main objective is to create a design that is sustainable to be used in a big family with a concept look and the ease of purpose-schedule. Big family do get an impact in a busy life so with this research we are determine to conclude a design-solver that can ease the burden in this new world. On-wards, with this new design from a local company brand, it is hoped that it can brings a big change to the transportation industry of our country.